MAGNETIC FORCE MICROSCOPE IMAGE EVALUATION OF MAGNETIC IRON OXIDE FLOPPY DISC WITH VARIOUS LIFT HEIGHTS - Nanda Shabrina; Mardiyanto Mardiyanto; Abu Khalid Rivai (Jurnal Sains Materi Indonesia, 2020)
Magnetic Force Microscope Image Evaluation of Magnetic Iron Oxide Floppy Disc with Various Lift Heights. One of the advantages of Scanning Probe Microscopes (SPM) or better known as the Atomic Force Microscope (AFM) is its ability to "see" in detail at the level of atoms and molecules, so as to improve understanding of how a system works and leads to new discoveries in areas such as life science, materials science, electrochemistry, polymer science, biophysics, nanotechnology and biotechnology. To understand about the MFM mode, amplitude, phase and topographic image, a piece of a flop-py disk as references sample was used in various lift heights. In this paper presented the principles of AFM work and explain the necessary components of such equipment. The MFM images were taken in floating operation method at different heights namely 30, 40 and 60 nm between the surface sample and Co-Cr cantilever tip. Result showed the distance between the cantilever tip to the sample surface influenced the image quality. The best amplitude image could be taken in 60 nm distance.